2016
DOI: 10.18632/oncotarget.13249
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided design of purine-based probes for selective Nek2 inhibition

Abstract: Nek2 (NIMA-related kinase 2) is a cell cycle-dependent serine/threonine protein kinase that regulates centrosome separation at the onset of mitosis. Overexpression of Nek2 is common in human cancers and suppression can restrict tumor cell growth and promote apoptosis. Nek2 inhibition with small molecules, therefore, offers the prospect of a new therapy for cancer. To achieve this goal, a better understanding of the requirements for selective-inhibition of Nek2 is required. 6-Alkoxypurines were identified as AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The activation of NEK2 is through the phosphorylation on its auto-phosphorylation sites such as (T170/S171 and T175) [37]. Carboxamide 11 is one of the best known selective inhibitors of NEK2 [38]. NEK2 has been reported to have a role in the progression of several malignancies, importantly in breast cancer, therefore devising the potential of an anticancer therapy [36,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of NEK2 is through the phosphorylation on its auto-phosphorylation sites such as (T170/S171 and T175) [37]. Carboxamide 11 is one of the best known selective inhibitors of NEK2 [38]. NEK2 has been reported to have a role in the progression of several malignancies, importantly in breast cancer, therefore devising the potential of an anticancer therapy [36,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Dose-response experiments with Nek7 WT and Nek7 SRS demonstrated that a Nek2 inhibitor, compound 51 [21], successfully inhibited both enzymes (Figure 2b,c). The apparent IC 50 values calculated in these experiments are 79.01 mM and 40.13 mM for Nek7 WT and Nek7 SRS , respectively.…”
Section: Engineering a Strong R-spine Mutant Of Nek7mentioning
confidence: 97%
“…Compound 51 inhibits Nek2 with an IC 50 of 1.42 mM, ∼50-fold more potently than Nek7 SRS [21]. To gain insights into this difference, we aligned the protein sequences (Figure 6a) and determined the crystal structure of Nek2 catalytic domain bound to compound 51 to a resolution of 2.0 Å (PDB code 6SK9; Figure 6b).…”
Section: Interaction Of Compound 51 With Nek7 and Nek2mentioning
confidence: 99%
See 2 more Smart Citations